FVC, FEV1 and FEV1% in Male Tobacco Industry Workers - Rahim Zahid, ATM Zoadur; Bari, MA; Sarkar, Chandra Rani; Begum, Shirin Akhter; Mosawuir, Abdullah Hil (Journal of Bangladesh Society of Physiologist, 2012)
Background: Tobacco industry workers are exposed to tobacco dust and smoke in their work places. Usually they have varying degree of impaired pulmonary functions, but the level of awareness about this occupational hazard among the tobacco industry workers and authorities are limited. Objective: The present study was conducted to observe the effects of exposure to tobacco dust and smoking on FVC, FEV1 and FEV1%. Methods: This cross-sectional study was carried out in the Department of Physiology, Rangpur Medical College, Rangpur, from July 2008 to June 2009 on 50 apparently healthy male smoker (Group B) and 40 non-smoker (Group C) tobacco industry workers with age range 20 to 45 years. For comparison,50 age and body surface area matched apparently healthy male non-smoker non-tobacco workers were also studied as Control(group A). The study groups were selected from different tobacco industries of Rangpur district and control group were selected from the surrounding community who belonged to lower socioeconomic condition. Pulmonary function parameters were measured by digital spirometer. Statistical analysis was done by unpaired‘t’ test . Results: Smoker tobacco workers had significantly lower percentage of predicted values of FVC, FEV1 and FEV1% than control subjects (p <0.001). In addition, they had significantly lower values of FEV1 and FEV1% than non-smoker tobacco workers (p <0.01). Conclusion: Pulmonary functions may be impaired in smoker tobacco workers. DOI: http://dx.doi.org/10.3329/jbsp.v6i2.9757 JBSP 2011 6(2): 90-93